Intervention Effectiveness An Analysis of the IMF's Role and Policy in Dealing with Ukraine's Monetary Crisis Post-Russian Conflict-2022 - giilangputraa; Gonda Yumitro (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
In most cases, geopolitical events are power struggles over a territory that cannot be resolved peacefully. These events carry risks such as war, terrorism, and inter-state tensions that disrupt international relations. Tensions and conflicts between countries are some examples of geopolitical risks that can disrupt international relations and affect the stock market. The Russia-Ukraine conflict is an example of a geopolitical case that made Ukraine experience a monetary crisis and suffered very complex losses. This study was conducted to explore the role of the IMF in stabilizing and restoring the economy in Ukraine during the post-war monetary crisis with Russia. The IMF served as an important provider of financial assistance to crisis-affected Ukraine through emergency loans, providing critical financial support to address urgent economic pressures. Important international cooperation is also a focus of the IMF in promoting global economic stability. This research highlights the IMF's role in providing emergency financial assistance for the stabilization of the Ukrainian economy affected by the conflict-induced monetary crisis. This article also discusses the role of the International Monetary Fund (IMF) in handling international financial crises, especially the global economic crisis. This article formulates the question of how the IMF's role in addressing the global economic crisis, especially in Ukraine with the aim of understanding the IMF's role in addressing the global economic crisis. Data is collected through literature research from various sources of books and journals as initial sources as well as relevant articles and news. Descriptive research is a type of qualitative research that aims to describe and interpret various elements, such as situations, conditions, development of perceptions, and consequences that occur.